Implementing Performance Reporting in Local Government: A Cross-Countries Comparison. Issue 3 (2nd July 2016) - Brusca, Isabel; Montesinos, Vicente
ABSTRACT: Providing information on economy, efficiency, and effectiveness is one of the most important innovations in local government management, with performance reporting emerging as a new component for accountability and decision-making. This article compares 17 countries to ascertain whether there is convergence between them, studying key issues in the implementation of performance reporting by local governments. It also identifies some lessons that can be of use to countries that want to implement or improve performance reporting systems. Findings show that there is no convergence in practice or results, and that institutional factors influence the implementation of performance reporting; in many countries, performance reporting has been introduced by central and regional governments as a mechanism to control local government activities in order to enhance performance. Austerity has underlined the importance of performance information, especially in Southern European countries, but more must be done before the full impact of performance reporting can be achieved.